Teacher Strategies in Managing Chemistry Learning Time to Improve Student Learning Achievement - Habibil Mazid; Latifah Rachmalia; Suyanta Suyanta; Endang Widjajanti (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to find out the teacher's strategy in managing ideal and effective chemistry learning time to improve students' learning achievement. The method used is literature research using secondary data reviewed from books, articles, and journals. The results show that chemistry learning conducted during the day has an ineffective impact on students in participating in learning, such as students not focusing, tired, sleepy, hungry, thus disrupting students' learning concentration. The hot classroom conditions during the day also make it difficult for students to accept the material taught by the teacher. Thus, morning time is considered an effective time or a good time to absorb chemistry learning materials. Students can also repeat or study the material again so that they understand better in the afternoon or evening. Thus, teachers can prepare teaching materials that have been adjusted to the time allocation so that learning is expected to run well and effectively